2017
DOI: 10.1371/journal.pone.0182302
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of multifarious plant growth promoting traits, antagonistic potential and phylogenetic affiliation of rhizobacteria associated with commercial tea plants grown in Darjeeling, India

Abstract: Plant growth promoting rhizobacteria (PGPR) are studied in different agricultural crops but the interaction of PGPR of tea crop is not yet studied well. In the present study, the indigenous tea rhizobacteria were isolated from seven tea estates of Darjeeling located in West Bengal, India. A total of 150 rhizobacterial isolates were screened for antagonistic activity against six different fungal pathogens i.e. Nigrospora sphaerica (KJ767520), Pestalotiopsis theae (ITCC 6599), Curvularia eragostidis (ITCC 6429),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 70 publications
(76 reference statements)
7
69
0
1
Order By: Relevance
“…2 ). Previous studies have shown that the cultivable rhizobacterial population in the tea rhizosphere is dominated by Bacillus genera 12 , 14 , 15 , 49 . Moreover, Bacillus genera are a dominant cultivable member in the rhizosphere soil of different plants, e.g., rice, wheat, tobacco, Panax notoginseng (Chinese ginseng), etc.…”
Section: Resultsmentioning
confidence: 99%
“…2 ). Previous studies have shown that the cultivable rhizobacterial population in the tea rhizosphere is dominated by Bacillus genera 12 , 14 , 15 , 49 . Moreover, Bacillus genera are a dominant cultivable member in the rhizosphere soil of different plants, e.g., rice, wheat, tobacco, Panax notoginseng (Chinese ginseng), etc.…”
Section: Resultsmentioning
confidence: 99%
“…isolated from halophytes have been extensively studied [55], very little is known about the bacterium S. equorum. Also, while PGP activity in the bacteria S. cohnii, S. capitis and S. warneri of the genus Staphylococcus has previously been described [56], to our knowledge, only two studies have characterized this activity in S. equorum strains Se1 and Se2 isolated from halophytes in Arabidopsis thaliana, which showed an increase in weight and root length [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…The tea clones were treated with 10 ml cell suspension by soil drenching at one-month intervals for three months and watered with sterile distilled water daily (Liotti et al, 2018;Zhao et al, 2018). All vegetative parameters such as shoot length, root length, shoot fresh and dry weight and root fresh, dry weight, chlorophyll content and soil parameter analysis were recorded and compared to control (Dutta et al, 2015b;Dutta and Thakur, 2017).…”
Section: Preparation Of Actinobacterial Inoculum and Treatmentmentioning
confidence: 99%
“…To date, rhizospheric and endophytic PGP bacteria have been explored and characterized from C. sinensis (Dutta et al, 2015b;Nath et al, 2015;Dutta and Thakur, 2017). However, very few data are available on tea endophytic actinobacteria especially in the North East region of India.…”
Section: Introductionmentioning
confidence: 99%